A three-dimensional twisted phononic crystal with omnidirectional bandgap based on inertial amplification by utilizing translation-rotation coupling. (22nd December 2022) - Ding, Wei; Chen, Tianning; Chen, Chen; Chronopoulos, Dimitrios; Zhu, Jian
Highlights: Three-dimensional twisted phononic crystal made of a single-phase material. Omnidirectional bandgap with continuously strong attenuation with filling ratio of the unit cell is just 22.4%. The bandgap can be tailored under the limitations of the quasi-constant stiffness and constant mass of the unit cell. Abstract: This work presents the design, manufacture, and experimental testing of a three-dimensional twisted phononic crystal made of a single-phase material. A broad, omnidirectional bandgap with continuously strong attenuation from 601 to 1504 Hz has been achieved, yet the filling ratio of the unit cell is just 22.4%. The theoretical study demonstrates that the inertial amplification based on the translation-rotation coupling is the cause of the bandgap. The translation-rotation coupling enables this phononic crystal to possess two stages of amplification. The tunability of the bandgap can be achieved in the first stage by intelligently regulating the contour of the lumped masses under the limitations of the quasi-constant stiffness and constant mass of the unit cell. The second stage allows the tilt angle of the ligaments to become a constantly tunable variable of the bandgap. This research comprehensively illuminates the 3D twisted phononic crystal based on inertial amplification and the approaches for tuning the bandgap in this class of phononic crystals.